Preferences, dedication and problematics generated by video games: A gender perspective - Ricoy, Carmen; Ameneiros, Aida (Revista Complutense de Educación, 2016)
Among the leisure activities of young boy/girls, it should be mentioned those associated with video games. Therefore, the central purpose of this study is to analyze the preferences of the group of adolescents with video games, as well as to know their dedication and problematics generated mainly considering the gender variable. This work is framed in a quantitativequalitative methodological approach, based on data collection with a questionnaire and the focus group technique. A total of 151 adolescents were involved in the study. 124 from the application of a closed questionnaire (62 men and 62 women) and 27 through the realization of 6 focus groups (17 men and 10 women). As results and conclusions, it is worth highlighting the existence of a distinct use of video games according to age and gender. In turn, women show greater responsibility with this activity, both in the time of dedication as in the election. Boys dedicate a lot of time to violent content video games, while girls prefer the strategy ones. In general, the game with video games does not generate substantial problematics and controversies, although some of the participants reflect bad humor’s manifestations. Finally, it must be indicated that video games practices in adolescence are limited to the mere fact of having fun, wasting the educational possibilities that this activity offers.